Pengaruh Biochar Sekam dan biourine Terhadap Pertumbuhan dan Produksi Tanaman Padi (Oryza sativa L.) - Choirul Anam; Mariyatul Qibtiyah; Dian Eka Kusumawati; Muhammad Rifqi Azwan (AGRORADIX : Jurnal Ilmu Pertanian, 2022)
This research activity aims to determine the different doses of husk biochar and biourine on the growth and production of rice plants. The activity was carried out in Bulubrangsi Village, Laren, Lamongan, from February to May 2022. The design is Factorial RAK. The first factor was the different doses of biochar husk consisting of control or without biochar, 5 t/ha, 10 t/ha. The second factor was the type of biourine which consisted of no biourine, cow biourine, goat biourine. There were 9 treatment combinations with 3 repetitions. In the vegetative phase observed plant height and number of leaves while the generative phase was plant wet weight, panicle length, dry seed weight, dry seed weight per plot, 1000 seed weight. Data processing was analyzed using ANOVA, if there is a significant difference then proceed with the BNT test. The conclusion showed that there was an interaction between the various doses of biochar and biourine treatments on plant height aged 14 and 28 days after planting, number of tillers aged 14 and 42 days after planting. panicle length ages 63, 70, 77, and 84 dap, as well as grain weight per 1000 seeds, fresh weight per plot, and fresh weight per hectare. The best treatment combination was rice husk biochar 10 t/ha and goat biourine.